Patient reported outcome measures (PROMs): examination of the psychometric properties of two measures for burden of symptoms and quality of life in patients with depression or anxiety. (19th May 2018) - Bech, Per; Austin, Stephen Fitzgerald; Lau, Marianne Engelbrecht
Abstract: Introduction: Patient-reported outcome measures (PROMs) for anxiety and depressive disorders are an important aspect of measurement-based care. Aim: The aim of the study was to perform a clinimetric analysis of two PROMs scales in patents with depression and anxiety. Methods: Patients completed a 10-item version (SCL-10) of the Symptom Checklist to measure burden of symptoms and a brief 5-item version of World Health Organization Well-being scale (WHO-5) to measure quality of life. T-scores were used to standardize the SCL-10 and WHO-5 in terms of being in need of treatment. The coefficient of alpha and the coefficient of homogeneity were used to evaluate the internal consistency or scalability respectively of SCL-10 and WHO-5. Effect size statistics and Spearman correlation coefficients were used to measure the effect of gender and age, respectively. Results: A total of 801 patients were recruited from two Danish mental health centers with anxiety or depression. The standardization of the SCL-10 and WHO-5 by T-scores indicated that a T-score of 65 corresponding to being moderately in need of treatment and a T-score of 75 to be severely in need of treatment. The coefficient of alpha and the coefficient of homogeneity were both found acceptable for SCL-10 and WHO-5. No gender or age factors were found being in operation. Conclusion: The results from the current study supported the use of the SCL-10 and WHO-5 as potential PROMs to capture symptom burden and quality of life within groups of people with anxiety or depression undergoing psychotherapy treatment.